Refractory migraine - Robbins, Lawrence (Henry Stewart Talks, 2023)
Refractory chronic migraine, Medical and non-medical approaches to refractory migraine treatment, Migraine preventives, Migraine abortives, Medication Overuse Headache (MOH), Factors that influence migraine, Treatment approaches, Opioids, Stimulants, Neuromodulation